DAMPAK SIKAP OVER PROTECTIVE ORANG TUA TERHADAP PERILAKU ANAK DI DESA WONOKAMPIR KECAMATAN WATUMALANG - Puja Afrianti, Nurhayati; Wardani, Sahar; Munawaroh, Hidayatu (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Parents are the first education for the child, but sometimes in providing parenting styles between parents with one another it must be different, for example the attitude of excessive parents to their children, this   excessive attitude is called an Over Protective attitude.   Parental Over Protective Attitude is an excessive attitude given by parents to their children Actually, this excessive attitude is considered a form of affection from parents, and is commonly done by parents to their children, but this is sometimes misinterpreted by children so they   Feeling uncomfortable and will certainly affect the child's own behavior. Because basically children need to explore their environment without  excessive  prohibitions and constraints carried out by their parents.  For this reason, we need to discuss what the impact of Over Protective parents on children's behavior.  Researchis carried out using qualitative methods and interview techniques